ВПЛИВ ТИПІВ ЛІСОРОСЛИННИХ УМОВ НА ЗАПАС ДЕРЕВИНИ ЛІСОУТВОРЮВАЛЬНИХ ПОРІД СТЕПОВОГО ПРИДНІПРОВ’Я УКРАЇНИ - Sytnyk, S. A.; Lovinska, V. M. (Ukrainian Research Institute of Forestry and Forest Melioration named after G. M. Vysotsky (URIFFM), 2018)
Introduction A large area and differences in site types of steppe zone lead to a wide range of habitat conditions and their climatic characteristics. Therefore, for reforestation and afforestation in the Steppe, the forest site types should be carefully considered. The actual target of forest ecosystems studies is to establish the features of forming of forest stands having maximum productivity and to determine the effect of abiotic factors on biomass accumulation processes. The aim of this paper is to analyze the age structure and determine a relationship between an average stand volume of Pinus sylvestris and Robinia pseudoacacia and forest site conditions (nutrient status and soil moistening). Materials and Methods The study was carried out in Scots pine and black locust plantations of Dnipropetrovsk Regional Department of Forestry and Hunting. The analysis of the age-related structure and average actual stand volume of Scots pine and black locust is conducted on the basis of subcompartment database of forest inventory content with an application of mathematical statistics methods. Results The largest area of black locust stands is in fairly fertile site type – 9596.5 ha (54.3 %); 53.1 % of the total stand volume is concentrated in this condition. In fertile site type Robinia pseudoacacia stands occupy more than a third of the area – 6732.2 ha (38.1 %) – with total stand volume of 40.8 %. The smallest area of this species (139.8 ha or 0.8 %) is concentrated in infertile pine site type – in the poorest soil conditions. Calculated values of the average stand volume for black locust of different age classes in various soil nutrient statuses (trophotopes) demonstrated the difference the studied parameters. The maximum values of average stand volume in trophotops account for 180 m? per ha in infertile pine site type; 202 m? per ha in fairly infertile pine site type; 178,9 m? per ha in fairly fertile site type; 180 m? per ha in fertile site type. These data demonstrate no difference in maximum values of the average stand volume between the poorest soil conditions and the most fertile ones. The decrease of the studied parameter is marked after black locust has attained the age of 75 years (in fairly fertile site type), 70 (in infertile pine site type), 65 (in fairly infertile pine site type and in fertile site type). Unlike black locust, ? of Scots pine stands are concentrated in fairly infertile pine site type with total stand volume of 3017.66 ths m3. It was mentioned that Scots pine forms stands in fertile site type in the smallest amount (1.2 %). In pine plantations, with increasing soil fertility from infertile pine site type to fertile site type, an increase of the average stand volume is noted. This parameter is higher in fertile site type compared to infertile pine site type by 27.5 %. The highest average pine stand volume is marked for stands of age class VIII in infertile and fairly infertile pine site types and for stands of age class VII in a fairly fertile site type. It is reported that in fertile site type the tendency to gradual increase of stand volume is saved to the oldest age class IX. The dependence of average wood volume on moisture conditions (hygrotop) is found. An average stand volume in the condition of fresh hygrotop is 181.6 % in relation to black locust’s volume produced in very dry hygrotop. A similar trend is found for other studied species – Scots pine, with a fixed 3 times prevalence of average volume in fresh and moist site type conditions compared to very dry ones. There is an increase in average stand volume of even-aged stands of pine and black locust with changing moisture conditions. However, in wet conditions, almost three times decrease of values of analyzed parameter is noted for pine. The black locust stands reach the maximum productivity (193.9 m3 per ha) at the age of 50 years old in condition of considerable moistening. At the same age the following indicators of the average stand volume are obtained: 121.0 m3 per ha (very dry hygrotop), 179.4 m3 per ha (dry hygrotop), 186.1 m3 per ha (fresh hygrotop), so there is a considerable influence of moisture conditions on efficiency of planting. Scots pine reached the maximum average stand volume in fresh site conditions in the age class VII and VIII (323 and 313 m3 per ha, respectively). It is determined that for Scots pine, similar to black locust, soil moist conditions have a significant impact on output stand volume per hectare. Beyond fifty years old for black locust and eighty years old for Scots pine forest stands, a tendency to increase stand volume with age is not established in different soil moisture type. In the optimal soil moisture conditions, an intensive growth is fixed for a long time for both studied species. With transformation from optimal to worst soil moisture conditions there is the rapid reduction of shoot, needle and leaves forming ability in the studied species, as well as of crown density, sizes of some specients and their resistance. Conclusions The largest area of black locust stands is in fairly fertile site type (54.3 %); a half of the total stand volume is concentrated in this condition. The maximum value of average stand volume accounts for 202 m? per ha in fairly infertile pine site type. The data demonstrate no difference in maximum values of the average stand volume between the poorest soil conditions and the most fertile ones. Most of Scots pine stands are concentrated in fairly infertile pine site conditions with total wood volume of 3017.66 ths m3. The highest average pine stand volume is marked for stands of age class VIII in infertile and fairly infertile pine site types and for stands of age class VII in a fairly fertile site type. An average stand volume for black locust in the fresh hygrotop is 181.6 % in relation to it in very dry hygrotop. A similar trend is found for Scots pine, with 3 times prevalence of average volume in fresh and moist site type conditions compared to very dry ones.